POTENSI KAWASAN KULINER PANTAI TAK BEROMBAK TERHADAP PENGEMBANGAN PARIWISATA DI KABUPATEN MAROS (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2021)
The main problem in this research is the Potential of Culinary Areas of Unwavering Beaches on Tourism Development in Maros Regency. The aim is to obtain data and information related to the Potential of Culinary Areas of Unwavering Beaches in Tourism Development in Maros Regency, the inhibiting factors of Unwavering Coastal Culinary Areas on Tourism Development in Maros Regency, and the strategy carried out by the Regency Tourism Office. Maros in developing the Culinary Area of Unwavering Beaches as a tourist area. The results of the research are: The Culinary Area of Unwavering Beach has four basic components of tourism development, namely, attraction, amenity, accessibility, and ancillary. The inhibiting factors are funds, arrangement, and management, supporting facilities and facilities, innovation and creativity of actors/sellers, promotions, awareness of sellers and visitors. The strategy was carried out by the District Tourism Office. Maros in developing the Unwavering Coast Culinary Area as a tourist area are: promotion, collaboration, involving the media, coaching, counseling, guidance, socialization, events, festivals, art and cultural performances, and will hold regular exhibitions.